Solitary juvenile xanthogranuloma of the eyelid. Review of the literature. - Milano, A.; Ingravallo, G. (European Journal of Pediatric Dermatology, 2023)
Juvenile xanthogranuloma (JXG) is a proliferation of dermal dendritic histiocytes. The skin is the organ most frequently affected, but other organs may also be affected, including the eye. Starting from a case of eyelid JXG, the authors systematically review all published similar cases in children under 13 years of age.